2018
DOI: 10.1186/s13567-018-0617-8
|View full text |Cite
|
Sign up to set email alerts
|

Gut colonization by a novel Clostridium species is associated with the onset of epizootic rabbit enteropathy

Abstract: Epizootic rabbit enteropathy (ERE) represents one of the most devastating diseases affecting rabbit farms. Previous studies showing transmissibility of disease symptoms through oral inoculation of intestinal contents from sick animals suggested a bacterial infectious origin for ERE. However, no etiological agent has been identified yet. On the other hand, ERE is associated with major changes in intestinal microbial communities, pinpointing dysbiosis as an alternative cause for the disease. To better understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
0
24
0
1
Order By: Relevance
“…Recent microbiota characterization studies using molecular approaches and modern sequencing techniques indicate that ERE could be caused by diet alterations or stress given by a wrong driving into the farm [30,33]. Additionally, ERE has been related to the proliferation of a new Clostridium species, Clostridium cuniculi [34], although this relation has not been experimentally validated yet. We cannot exclude that many of the cases studied in growing rabbits are related to this severe disease, but we cannot confirm those cases as ERE either.…”
Section: Discussionmentioning
confidence: 99%
“…Recent microbiota characterization studies using molecular approaches and modern sequencing techniques indicate that ERE could be caused by diet alterations or stress given by a wrong driving into the farm [30,33]. Additionally, ERE has been related to the proliferation of a new Clostridium species, Clostridium cuniculi [34], although this relation has not been experimentally validated yet. We cannot exclude that many of the cases studied in growing rabbits are related to this severe disease, but we cannot confirm those cases as ERE either.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Bauerl, et al () suggested that a decrease in the abundance of Ruminococcus and Alistipes in the gut microbiota of post‐weaning rabbits was related to the development of Epizootic rabbit enteropathy (ERE), one of the most devastating diseases affecting rabbit farms. Conversely, Djukovic, et al () indicated that the disease developed due to an increase in the abundance of Clostridium cuniculi .…”
Section: Introductionmentioning
confidence: 99%
“…This may suggest that poor quality or foul nectar may pre-dispose overgrowth of C. perfringens, as occurs in rabbits with epizootic rabbit enteropathy in which dysbiosis (imbalance of natural gut flora) and Clostridium spp. overgrowth have been proposed as associated risk factors (36).…”
Section: Discussionmentioning
confidence: 99%